Association Between Central Sleep Apnea and Left Atrial Enlargement in Snoring Patients with Preserved Ejection Fraction - Sun X; Wang Y; Wu C; Gao Y (Nature and Science of Sleep)
Xinghe Sun,1,* Yang Wang,1,* Chaoqun Wu,2,3 Yinghui Gao4 1Department of Cardiology, Peking University International Hospital, Beijing, People’s Republic of China; 2National Clinical Research Center of Cardiovascular Diseases, State Key Laboratory of Cardiovascular Disease, Fuwai Hospital, National Center for Cardiovascular Diseases, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, People’s Republic of China; 3Department of Epidemiology & Biostatistics, School of Public Health, Peking University, Beijing, People’s Republic of China; 4Department of Sleep Medicine, Peking University International Hospital, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chaoqun Wu, National Clinical Research Center of Cardiovascular Diseases, State Key Laboratory of Cardiovascular Disease, Fuwai Hospital, National Center for Cardiovascular Diseases, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, People’s Republic of China, Email wuchaoqun@fuwai.com Yinghui Gao, Department of Sleep Medicine, Peking University International Hospital, Life Park Road No.1 Life Science Park of Zhong Guancun, Beijing, People’s Republic of China, Email gaoyinghui1@pkuih.edu.cnBackground: Central sleep apnea (CSA) significantly impacts cardiovascular health, linking it to left atrial enlargement, atrial fibrillation, and impaired cardiac function in heart failure patients with reduced ejection fraction (EF). However, the relationship between CSA and left atrial size in individuals with preserved EF remains underexplored.Objective: This study aims to examine the relationship between left atrial size and CSA in snoring patients with preserved EF.Methods: An observational study was conducted involving 341 consecutive snoring patients from a cardiology department who underwent overnight polysomnography (PSG) and echocardiography. Patients with EF below 50%, pulmonary diseases or neuromuscular disorders were excluded. CSA was defined as a central apnea-hypopnea index (CAHI) of five or more events per hour. Inverse probability of treatment weighting (IPTW) and logistic regression models were employed to evaluate the relationship between CSA and left atrial size.Results: Among the 341 patients, 33 (9.68%) were diagnosed with CSA, with a higher prevalence in males (10.0%) than females (8.91%). Left atrial enlargement (LAE) was observed in 172 patients (50.44%), predominantly in females (71.29%). CSA patients demonstrated significantly higher apnea-hypopnea index (AHI) (49.2/h vs 26.75/h, p < 0.01) and oxygen desaturation index (ODI) (44.9 vs 22.85, p < 0.01), alongside more sleep time with oxygen saturation < 90% (6.6% vs 2.35%, p = 0.01). Echocardiographic evaluations revealed that CSA patients had a greater left atrial anterior-posterior diameter(LAD-ap 42.73 ± 13.01 mm vs 38.15 ± 4.58 mm, p < 0.01) and a higher frequency of LAE (69.7% vs 48.38%, p = 0.02). Males with CSA had a significantly increased risk of LAE (OR: 4.54; 95% CI: 1.45– 14.2) after IPTW adjustment, with significant associations persisting among those with risk factors such as smoking and dyslipidemia.Conclusion: This study highlights a significant association between CSA and left atrial enlargement in males with preserved EF, suggesting that CSA may contribute to atrial remodeling even without reduced ejection fraction.Keywords: central sleep apnea, left atrial enlargement, preserved ejection fraction